(untitled) (Training and Practice : Journal of Educational Sciences, 2020)
Social work as a profession and practice is an essential and determining area of human problem solving. In terms of its methods and general knowledge, social work is also a highly complex and human-specific helping profession in the triangle of problem, resource and autonomy. The legitimate role of the triangle is made up of interpersonal interactions. The accumulated practice and experience are an indispensable part of the knowledge organ, which gives the users maturity and constant ability for development. The professional personality, with its contextual coherence, is at the centre of the development, which is also the most important instrument of support. Reflection, internal and external, is a direct approach in the context of social work. It helps the user to achieve confident and rich experience of the personality.